Despite Good Correlations, There Is No Exact Coincidence between Isometric and Dynamic Strength Measurements in Elite Youth Soccer Players - Carl-M. Wagner; Konstantin Warneke; Christoph Bächer; Christian Liefke; Philipp Paintner; Larissa Kuhn; Torsten Brauner; Klaus Wirth; Michael Keiner (MDPI AG, 2022)
Speed strength performances are substantially dependent on maximum strength. Due to their importance, various methods have been utilized to measure maximum strength (e.g., isometric or dynamic) with discussed differences regarding transferability to sport-specific movements dependent upon the testing procedure. The aim of this study was to analyze whether maximum isometric force (MIF) during isometric back squats correlates with maximum strength measurements of the one repetition maximum (1RM) in the squat, with countermovement jump (CMJ) performance, and with drop jump (DJ) performances in elite youth soccer players (n = 16, 18.4 ± 1.5 [range: 17-23] years old). Additionally, concordance correlation coefficients (CCC, [ρc]) between isometric and dynamic measurements were calculated to verify whether one measurement can actually reproduce the results of the other. To improve comprehension, differences between isometric and dynamic testing values were illustrated by providing differences between both testing conditions. For this, the mean absolute error (MAE) and the mean absolute percentage error (MAPE) were calculated. To reach equality in scale, the 1RM measures were multiplicated by 9.81 to obtain a value of N. The 1RM demonstrated correlations of τ = |0.38| to |0.52| with SJ and CMJ performances, while MIF demonstrated correlations of τ = |0.21| to |0.32|. However, the correlations of both 1RM and MIF with the DJ reactive strength index (RSI = jump height/contact time) from different falling heights were of no statistical significance. The data showed significant correlations between both the absolute (τ = |0.54|) and the relative (τ = |0.40|) performances of 1RM and MIF, which were confirmed by CCC of ρc= |0.56| to |0.66|, respectively. Furthermore, the MAE and MAPE showed values of 2080.87 N and 67.4%, respectively. The data in this study show that, despite good correlations, there is no exact coincidence between isometric and dynamic strength measurements. Accordingly, both measurements may only represent an estimation of maximal strength capacity and cannot be substituted for each other. Therefore, maximal strength should be tested by using high similarity in the contraction condition, as it is used in the training process to counteract underestimation in strength because of unfamiliarity with the testing condition.